2021
DOI: 10.1097/ajp.0000000000000981
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Peripheral Nerve Stimulation for Treatment of Acute/Subacute Herpes Zoster-related Trigeminal Neuralgia

Abstract: add state sales tax. The GST tax of 7% must be added to all orders shipped to Canada (Wolters Kluwer Health, Inc. GST Identification #895524239, Publications Mail Agreement #1119672). Subscription prices outside the United States must be prepaid. Prices subject to change without notice. Visit us online at www.lww.com.Individual and in-training subscription rates include print and access to the online version. Institutional rates are for print only; online subscriptions are available via Ovid. Institutions can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“… 28 Gasserian ganglion block provides sedative effect, which reduces the excessive excitation of sympathetic nerve and the release of neurotransmitters. 9 Lidocaine makes the lesion area reach a painless state quickly and plays the role of muscle relaxant, vasodilator and improved microcirculation. 29 Dexamethasone provides anti-inflammatory, analgesic and immunosuppressive effects and prolongs the effect time when combined with local anesthetics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 28 Gasserian ganglion block provides sedative effect, which reduces the excessive excitation of sympathetic nerve and the release of neurotransmitters. 9 Lidocaine makes the lesion area reach a painless state quickly and plays the role of muscle relaxant, vasodilator and improved microcirculation. 29 Dexamethasone provides anti-inflammatory, analgesic and immunosuppressive effects and prolongs the effect time when combined with local anesthetics.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Acute zoster-related trigeminal neuralgia presents as facial pain within 30 days of zoster onset, characterized by severe burning pain and tingling in the skin of the innervated area, along with the occasional tearing or stabbing pain. 8 , 9 Subacute zoster-related trigeminal neuralgia is described as facial pain from 31 to 90 days after zoster onset. 8 , 9 Trigeminal postherpetic neuralgia (TPHN) is defined as dermatomal pain after zoster onset, resulting from acute and subacute zoster-related trigeminal neuralgia, which persists for over 3 months and is the most common and the most severe type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 4 As HZ virus invades gasserian ganglion (GG) or trigeminal nerve, the reactivation and replication of the virus would cause neuronal edema and necrosis of the infected ganglion and nerve, leading to zoster-related trigeminal neuralgia (TN), 5 , 6 which accounts for approximately 15%-20% HZ patients. 7 Nowadays it is also a challenging and intractable neuropathic pain, which is lack of completely effective treatment. In addition, previous studies indicated that zoster-related trigeminal pain was more refractory than herpetic neuralgia in areas from the cervical to lumbosacral level.…”
Section: Introductionmentioning
confidence: 99%
“…Krohel зі співавт. ще в 1976 році описали хронічну HSV-1-індуковану (Herpes simplex virus, HSV, вірус простого герпесу) нейропатію трійчастого нерва [23] [24]. Ураження структур мезолімбічної системи головного мозку, яке відбувається при вірус-індукованому скроневому медіанному склерозі [55] або автоімунних лімбічних енцефалітах, зумовлених автоантитілами до автоантигенів нейронів гіпокампів [17], може призводити до порушення механізмів центральної регуляції болю при тригемінальних невралгіях у людей.…”
unclassified